2020
DOI: 10.1186/s12903-020-1047-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a modified version of the Spanish Geriatric Oral Health Assessment Index (GOHAI-SP) for adults and elder people

Abstract: Background: The Geriatric Oral Health Assessment Index (GOHAI) was developed and validated in 1990 and translated into Spanish in 1999. Since then, the original version has been used in numerous studies, but it has not been re-evaluated in terms of language in the new generations of older adults. The purpose of this study is to confirm the validity of the Spanish version of the Geriatric Oral Health Assessment Index (GOHAI-SP) after three decades to be used as part of an ongoing field trial. Methods: The GOHAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…18,19,22,30 This study was carried out on 408 participants which are comparable to the Iranian study (417) 22 and in other similar studies, the range of the participants varies from 101 to 288 subjects. 17,20,30 The mean GOHAI-U score (40.2) in this study was close to the mean GOHAI score in Jordan (40.9) and Turkish (42.5) studies, 23,25 but lower than studies in developed countries like the USA (52.5), Germany (53.0), Sweden (49.8) and France (46.4) 20,21,24 and relatively higher score then studies in India (32.02) and Saudi Arabia (32.1). 19,23 The majority of participants in this study had no oral prostheses (70.8%), and previous reports suggested that having dentures (full and partial) can significantly affect QoL in a positive way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19,22,30 This study was carried out on 408 participants which are comparable to the Iranian study (417) 22 and in other similar studies, the range of the participants varies from 101 to 288 subjects. 17,20,30 The mean GOHAI-U score (40.2) in this study was close to the mean GOHAI score in Jordan (40.9) and Turkish (42.5) studies, 23,25 but lower than studies in developed countries like the USA (52.5), Germany (53.0), Sweden (49.8) and France (46.4) 20,21,24 and relatively higher score then studies in India (32.02) and Saudi Arabia (32.1). 19,23 The majority of participants in this study had no oral prostheses (70.8%), and previous reports suggested that having dentures (full and partial) can significantly affect QoL in a positive way.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] Before using any measure in a region or community with a different language and culture, it needs to undergo a procedure of translation, cultural adaptation, and tested for its validity and reliability. 15 Since its development, GOHAI has been translated and used widely in different populations (China, Malaysia, Iran, Sweden, Germany, Spain, France, Turkey, Japan, India, Jordan, and Saudi Arabia) and shown to have an acceptable psychometric properties 9,[16][17][18][19][20][21][22][23][24][25] However, despite its global popularity, a GOHAI is never translated and used in Pakistani elder population for assessing their OHRQoL. Therefore, the aim of the study was to develop the Urdu version of the Geriatric Oral Health Assessment Index (GOHAI-U), assess its reliability and validity, and demonstrate its psychometric properties with regard to OHRQoL in the elder Pakistani population.…”
Section: Introductionmentioning
confidence: 99%
“…The MELD score in the present study was calculated with the blood creatinine, bilirubin, and INR (international normalized ratio) values recorded at the time of listing for liver transplant surgery by the transplant team. MELD scores were divided into three groups: low (MELD < 10), medium (MELD [11][12][13][14][15][16][17][18], and high (MELD 19-40).…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…Furthermore, the GOHAI (Geriatric Oral Health Assessment Index) questionnaire is also an assessment tool for examining the relationship between oral diseases and quality of life in the elderly. This tool also addresses three main dimensions: (1) physical function, (2) psychosocial function, and (3) pain or discomfort [15]. Accordingly, considering the importance of oral health in liver transplant success and its consequent impact on the quality of life of these patients, we decided to design this study to assess the effects of oral health status and disease severity on OHRQOL of candidates for liver transplant surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Há vários exemplos desses questionários validados na literatura, e a sua escolha deve se basear em informações do público-alvo e nos objetivos da pesquisa. Uma dessas medidas é o The Geriatric Oral Health Assessment Index (GOHAI), um índice criado para avaliar as limitações bucais e a satisfação com a saúde bucal do público idoso 7,8 .…”
Section: Introductionunclassified